Scaling up food loss and waste reduction programs in Indonesia - Rasya Athalla Aaron; Ibnu Budiman (Center for Indonesian Policy Studies (CIPS), 2025)
Securing national regulation(s) on food loss and waste (FLW) is essential for the effective, comprehensive, and unified management and policy implementation of FLW, ensuring standards are consistent countrywide and local initiatives and targets are aligned with national waste reduction goals. Providing government incentives, e.g. local incentive funds (Dana Insentif Daerah), to food loss and waste (FLW) reduction initiatives can boost food rescue programs and encourage collaboration with development partners. Coordinated efforts (e.g. task forces) among government, businesses, NGOs, and other development partners are required to align interests and promote sustainable, impactful practices. FLW reduction strategy must be incorporated in the school meal program (MBG) policy and guidelines.
Keywords: 330